Critical Analysis of The Romanticism of The Novel “The Fault In Our Stars” by Using Reader Response - Puspita Kumala Dewi; Fathin Aulia Rahma Elhada; Wahyu Indah Mala Rohmana (English Language and Literature, 2023)
The aim of this method is to describe the state of a situation in a systematic and factual manner. This makes it easier to understand the love language from the novel. In conducting this research, the writer uses a qualitative approach as the focus of the research method. From the data that has been analyzed, there are 5 body language points written in the hall of the building c. According to Gary Chapman, there are 5 kinds of love language, including physical touch, word affirmation, quality time, giving gifts, and acts of service. In the novel The Fault in Our Stars, there are several love languages or romanticism written in it. The first love language is physical touch. Love language with romanticism has a very strong correlation. Romance is a treat that someone does to their loved ones in order to express the feelings they feel. Romance also includes act services such as giving attention, giving something to each other and doing small things that can make a couple happy. When someone really loves their partner, then automatically that person will do romantic things to their partner. Everyone has a different way of doing romantic things. Examples of romantic things you can do are stroking your partner's hair, giving a little of the food you have to your partner, saying romantic sentences like "I do love you", "I miss you", "You always look beautiful".